2009
DOI: 10.2165/00007256-200939040-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Placebo Effect in Sports Performance

Abstract: The placebo effect, with its central role in clinical trials, is acknowledged as a factor in sports medicine, although until recently little has been known about the likely magnitude and extent of the effect in any specific research setting. Even less is known about the prevalence of the effect in competitive sport. The present paper reviews 12 intervention studies in sports performance. All examine placebo effects associated with the administration of an inert substance believed by subjects to be an ergogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
195
3
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(211 citation statements)
references
References 29 publications
8
195
3
5
Order By: Relevance
“…Studies that have examined the placebo effect, using inert substances believed to be ergogenic, also report that false positive beliefs elicit performance improvements [36] . Altering perceptions of the exercise requires an element of deception in order to prevent the threat to internal validity from expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the placebo effect, using inert substances believed to be ergogenic, also report that false positive beliefs elicit performance improvements [36] . Altering perceptions of the exercise requires an element of deception in order to prevent the threat to internal validity from expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Outro ponto ressaltado em alguns estudos é que o efeito do IPC poderia ter base motivacional 18,20 , visto que alguns deles mostram que a aplicação da manobra de IPC repetidas vezes minimiza o desempenho físico 19,36 ao longo do tempo. O efeito placebo, altamente reconhecido em estudos sobre o desempenho humano 37 , portanto, precisa ser controlado e considerado na interpretação e tomada de decisão sobre qualquer estratégia 19,25 . O tempo entre a manobra de IPC e o início do exercício ou teste também deve ser analisado, visto que estudos oriundos da fisiologia clínica propõem que os benefícios do IPC podem durar mais que 24 horas 14 .…”
Section: Métodos De Investigação E Interpretação Dos Resultadosunclassified
“…Further this knowledge can be practically applied in the treatment and interaction with athletes in the context of sports medicine, physical therapy and nutritional interventions. Finally, investigating the placebo effect in the context of motor performance elicited by the administration of a nutritional ergogenic aid has implications not only for sports and the development of training strategies, 26,75 but also for the direction of future performance research and the controversial topic of (placebo) doping in sports, 76 raising not only ethical but also legal issues.…”
Section: Resultsmentioning
confidence: 99%
“…A review of 12 studies looking at sports performance changes following interventions noted placebo responses between -7.8% and +50.7%. 26 In 2008, Pollo, et al were able to show that placebo-induced expectations of better performance can reduce the perception of fatigue while increasing muscle work, suggesting top-down modulation of exercise performance via central fatigue mechanisms. 27 A recent study investigated elite athletes' attitudes toward placebo induced per-formance enhancement and concluded that roughly 50% of elite athletes have experienced placebo effects, the majority believes in the possible ergogenic effect of placebos and those with past placebo experiences would not mind them being more widely used.…”
Section: Placebo Effect and Ergogenic Aidsmentioning
confidence: 99%